Assessment of reserve effect in a marine protected area: the case study of the Professor Luiz Saldanha Marine Park (Portugal) - Sousa, Inês Isabel (2013)
Dissertação de mest., Biologia Marinha (Ecologia e Conservação Marinhas), Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2011